2018
DOI: 10.1016/j.diabet.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 receptor ST2 deficiency attenuates renal ischaemia–reperfusion injury in euglycaemic, but not streptozotocin-induced hyperglycaemic mice

Abstract: Our data suggest that the IL-33/ST2 pathway exerts differential effects depending on the glucose environment, opening-up new avenues for future research on alarmins and diabetes in ischaemia-related diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…In addition, in the diabetic group, UAE, and A/C ratio were significantly higher than in the control rats. These results come in line with (Sehnine et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, in the diabetic group, UAE, and A/C ratio were significantly higher than in the control rats. These results come in line with (Sehnine et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, in the diabetic group, UAE, and A/C ratio were significantly higher than in the control rats. These results come in line with (Sehnine et al, 2018). To explain the mechanisms beyond renal injury induced by diabetes induction; total NO, oxidative stress markers, and inflammatory markers measured in the renal tissue.…”
Section: Discussionsupporting
confidence: 83%
“…IL-33 acting as an alarmin triggers and amplify the activation of NKT cells through innate as well as adaptative immune responses. Similar to NK cell, NKT cells constitutively express on their surface the ST2 chain that is specific to the IL-33 receptor thereby contributing as a co-stimulatory agent to Th1 (IFN-γ), Th2 (IL-4) and Th17 (IL-17A) NK and NKT cell cytokine production [90,91]. In our study, we could not depict Th17 responses following either IL-12 or IL-23 stimulation of NK and NKT cells.…”
Section: Pathophysiologic Role Of Il-33 In Sjogren's Syndromementioning
confidence: 63%
“…Several groups have generated IL1RL1-deficient mice for the genetic deletion of the IL-33 receptor, which is encoded by the IL1RL1 gene. Sehnine et al used the IL1RL1 knockout mice to demonstrate that streptozotocin (STZ)-induced hyperglycemic mice exhibited an increased urinary albumin excretion [77]. At 24 h post-IRI, the ST2 knockout mice exhibited markedly reduced plasma creatinine, blood urea nitrogen (BUN), and tubular injury.…”
Section: Potential Applications and Caveats Of Therapeutic Targeting mentioning
confidence: 99%
“…At 24 h post-IRI, the ST2 knockout mice exhibited markedly reduced plasma creatinine, blood urea nitrogen (BUN), and tubular injury. However, this protective effect was mitigated in the ST2-induced diabetes mellitus (DM) mice [77]. This suggested that the high glucose environment may impair the IL-33/ST2-mediated renal protective function.…”
Section: Potential Applications and Caveats Of Therapeutic Targeting mentioning
confidence: 99%